SOCIOLOGY OF LAW AS A MEANS OF SOCIAL ENGINEERING IN RELATION TO CYBER CRIME - Andreas Kevin Simanjorang; Catharina Dewi Wulansari (CV. RADJA PUBLIKA, 2025)
The existence of law can be a tool for organizing, influencing, and renewing community life. Community thought patterns and behavior can be guided in a righteous and constructive direction if the law can be empowered as a strategic force to influence them.Law has become a crucial instrument for controlling and countering social engineering, particularly in the digital 4.0 era, where cybercrime is on the rise. This paper aims to examine the role of law as a tool for social change in everyday life. This paper utilizes a literature review (library research) method.